Generative AI Tools in Customer Service – Beyond the Hype of 'Prompt Engineering' - Thedda Deecke; Sina Wulfmeyer; Marcus Schögel (Marketing Review St.Gallen, 2023)
The adoption of artificial assistant tools (AAT) powered by generative artificial intelligence and large language models to support frontline employees (FLEs) opens up promising new use cases while also introducing changing skillset requirements and new challenges (e.g., in compliance and data security). In this paper, the authors explore AAT implementation in a customer contact center, drawing conclusions from a qualitative study of practical use cases, necessary FLE skills and data security requirements and solutions. Recommendations are provided for implementing AATs using the GPT-3.5 Turbo API.
Keywords: 650